Transcatheter closure of calcified patent ductus arteriosus in older adult patients: Immediate and 12‐month follow‐up results. (22nd November 2016) - Gu, Xinghua; Zhang, Qiuwang; Sun, Hourong; Fei, Jianchun; Zhang, Xiquan; Kutryk, Michael J.
Abstract: Objective: To present our experience in transcatheter closure of calcified patent ductus arteriosus (PDA) in older adult patients, which has rarely been reported. Patients: From 2009 to 2014, a total of 16 patients (median age 58 years) with calcified PDA underwent transcatheter closure in our center. All patients were symptomatic with major symptoms being exertional dyspnea (in 12), palpitations (in 8), and fatigue (in 5). A continuous murmur was heard in all patients. The median ductus diameter was 4 mm (range 3–7 mm). The median Qp/Qs was 1.6 (range 1.4–2.9). Interventions: Transcatheter closure was performed for all patients. The size of the occluder selected was 2–3 mm greater than the narrowest portion of PDA. We experienced difficulties in advancing the multipurpose catheter through the calcified duct in about one third of patients (5/16). Considering that calcified tissue has a greater tendency to rupture, hence, to close PDA in these patients, they adopted the retrograde wire‐assisted technique and modified the procedure to reduce the shear stress of sheath and avoid any sheath kinking. For the remaining 11 patients, the advancement of the multipurpose catheter through the calcified duct was smooth and the conventional antegrade approach was applied. Outcome Measures: Clinical examination, standard 12‐lead electrocardiography, chest x‐ray, and transthoracic echocardiography were performed before hospital discharge, at 1‐, 3‐, 6‐, and 12‐months follow‐ups. Results: All PDAs were successfully closed. There were no deaths. Three patients had a trivial residual shunt, with one also having intravascular hemolysis. Following pharmacological treatment, hemolysis signs vanished at 7 days postprocedure. The trivial residual shunt disappeared in all three patients at 3‐month follow‐up. No new‐onset residual shunt, device embolization, device dislocation, infective endocarditis, or embolism was observed at all follow‐up time points. Conclusion: Successful closure of calcified PDA with few complications in older adult patients was achieved using the duct occluder.